2017
DOI: 10.5296/ber.v7i2.12071
|View full text |Cite
|
Sign up to set email alerts
|

How Can We Interpret the Estimates of the Full BEKK Model with Asymmetry? The Case of French and German Stock Returns

Abstract: This study conducts careful interpretations of the model parameters from the full Baba-Engle-Kraft-Kroner (BEKK) model with asymmetric effects. This study also includes a case study, in which we interpret the full BEKK model parameter estimates from the empirical examinations using French and German stock index returns. More concretely, in this paper, we firstly examine the model formula and obtain general interpretations of the full BEKK model parameters. This shall be particularly helpful to understand not o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…This paper investigated the effects of structural breaks on stock return volatility persistence by using the US and UK stock market index return data. In economics and finance, GARCH models are highly useful and important as Guo (2017), Tsuji (2014Tsuji ( , 2016bTsuji ( , 2016cTsuji ( , 2017aTsuji ( , 2017bTsuji ( , 2018b, and many other studies demonstrated. Based on this, applying two kinds of GARCH models of standard GARCH and EGARCH models, we derived the following interesting findings.…”
Section: Discussionmentioning
confidence: 99%
“…This paper investigated the effects of structural breaks on stock return volatility persistence by using the US and UK stock market index return data. In economics and finance, GARCH models are highly useful and important as Guo (2017), Tsuji (2014Tsuji ( , 2016bTsuji ( , 2016cTsuji ( , 2017aTsuji ( , 2017bTsuji ( , 2018b, and many other studies demonstrated. Based on this, applying two kinds of GARCH models of standard GARCH and EGARCH models, we derived the following interesting findings.…”
Section: Discussionmentioning
confidence: 99%
“…This paper quantitatively investigated the relations of structural breaks and volatility spillovers by using the stock return data of the US S&P 500 and Canadian Toronto stock exchange composite index. In the fields of business and finance, it is well-known that GARCH approach is highly useful and beneficial as Bollerslev (1986Bollerslev ( , 1990, Nelson (1991), Glosten et al (1993), Engle and Kroner (1995), Tsuji (2016Tsuji ( , 2017aTsuji ( , 2017b, and many other extant studies signified. Based on this, applying the spillover MGARCH models without and with structural break dummy variables, this study derived the following interesting evidence.…”
Section: Summary Implications and Conclusionmentioning
confidence: 99%
“…With regard to the mean equations, a positive A(i,i)A(i,j) and A(i,j) suggest a shock to the ith variable has positive effects on all variable covariances in the next period. Concerning the variance and covariance a positive B(j,j) B(i,j) means an increase in the ith variable has a positive effect on the variables covariances in the next period (Tsuji, 2017). 5-4.18472 0.00000 C(5) -3.71761 0.00000 C(6) 7.016273 0.00000 C(6) -6.71818 0.00710 C 711.67473 0.00000 C 713.24437 0.00000…”
Section: The Estimated Modelmentioning
confidence: 99%